The Use of DigSilent Power Factory Simulator for “Introduction into Power Systems” Lectures - Astapov Victor; Palu Ivo; Vaimann Toomas (Electrical, Control and Communication Engineering)
The first-year students at the technical universities often face the problem of using the previously acquired knowledge at a higher level required by engineering education. To solve this problem, the authors developed a series of lectures dedicated to establishing theoretical background, based on simulations in DigSILENT Power Factory software. In the lectures, the physical values and quantities as well as the purpose and characteristics of the power equipment are explained on the example of the simple models.